Physicochemical and Rheological Characterization of Malaysian Rice Flours and Starches - Mustapha, Nor Afizah (2007)
Physicochemical and rheological properties of flours and starches from nine Malaysian rice varieties (seven MR and two MRQ) were investigated. The physicochemical properties determined were swelling power (SP), carbohydrate leaching (CL), gelatinization, pasting, and textural characteristics, whereas the rheological properties studied were steady and dynamic shear. The varieties can be classified into low, intermediate and high amylose (AM) rice and also into intermediate and high-gelatinization temperature (GT). The varieties can be clearly grouped into MR and MRQ varieties based on setback (SB) and final (FV) viscosities and textural analysis. MRQ possessed greater SB, FV and gel hardness but lower gel adhesiveness, whereas, MR varieties showed the opposing results. An increase in AM increased the SB, FV, gel hardness, apparent viscosities(ηa) at and above 8% and 6% for flours and starches, respectively), and, storage modulus (G’), loss modulus (G”), complex modulus (G*) and complex viscosity (η*), but decreased the SP, To, Tp, Tc, enthalpies (ΔH), peak viscosity (PV), breakdown (BV), gel adhesiveness, and tan δ. ηa of the flours and starches increased with increasing solid concentrations and the viscosities depended on concentration regimes. Close-packing concentration was observed at concentration ranges of 6.4-8.7% (w/w) and 3.4-4.7% (w/w) in both flour and starch pastes, respectively. Cross-over concentration in the viscosity of the flour (5.6–7.9%, w/w) and starch (2.3–3.4%, w/w) pastes between high (MR) and low (MRQ) swelling varieties was found to occur at around the close-packing concentration. G’, G”, G* and η* increased whereas tan δ decreased with storage. Dynamic viscoelastic measurements of the starch and flour pastes before and after cooling indicated strong gel characteristics, with MRQ giving stronger and elastic gels. Cox-Merz rule was applicable in the rice starch only at certain concentrations. However, η* could provide a reasonable estimate of ηa. The interplay of starch granular properties and AM contents primarily influence the physicochemical and rheological characteristics of rice flours and starches, whereas the presence of flour components especially proteins significantly influenced the flour properties. MRQ34 exhibited interesting properties that possessed similar characteristics to the high AM variety (MRQ74). Strong correlation observed between the physicochemical (SP, FV, hardness and adhesiveness) and rheological (ηa, G’, G”, G* and η*) characteristics provide a means of predicting of the physicochemical properties via rheological methods and vice versa.